Lower Ureteral Obstruction and Leakage in the First Month Following Renal Transplantation - Abdul muhsin, Ausama i Saad; Alnasiri, Usama S; Rifat, Usama N (AL-Kindy College Medical Journal, 2007)
Background: Transplantation has revolutionizedtreatment of end- stage renal disease (ESRD) by provingmore cost effective than hemodialysis, with a lowermorbidity and improved quality of life.Objective: To evaluate the development of thesecomplications in the first month postoperatively andcorrelate their development to the type of donationwhether related or unrelated.Methods: Fifty (50) patients aged (15-62) years, with amean age (34.46 ± 12.4 SD) years with (ESRD), whounderwent renal transplantation from September 2000 toOctober 2002, were followed-up for one monthpostoperatively clinically and by assessment of renalfunction tests, sonographic and Doppler examinations.Ureteral obstruction was considered in those patients whohad allograft dysfunction, ultrasonic evidence ofperitransplant collection, moderate-severe dilatation ofupper urinary tract of transplanted kidney andpostoperative ipsilateral or bilateral leg edema. Ureteralleakage was considered in those patients who hadpersistent drainage of urine with or without allograftdysfunction. Two patients were excluded from the followup due to death in the first 24-hour postoperatively.Results: Six (6) patients (12.5% of cases) developedureteral obstruction due to peri-ureteral fluid collection. Infive patients the collection decreased and upper urinarytract dilatation improved gradually, as shown byultrasound, on watchful waiting. One patient had surgicalevacuation of a large hematoma. Four (4) patients (8.3%of cases) developed ureteral leakage. The leakage stoppedin one patient after keeping the urethral catheter for alonger period. Three patients had surgical exploration dueto persistent urinary leakage. Redo implantation ofallograft ureter was done in two cases.Development of ureteral complications was comparedwith the type of donation (related or unrelated). Thecomparison was not statistically significant.Conclusions: The development of ureteralcomplications in not related to the type of donation.Extravesical ureteral anastamosis with the use of a stent isless likely to be associated with postoperative ureteralcomplications.